2008
DOI: 10.1017/s0003598x00096861
|View full text |Cite
|
Sign up to set email alerts
|

Basalt bifacial tool production in the southern Levant: a glance at the quarry and workshop site of Giv'at Kipod, Israel

Abstract: The authors describe the discovery of a Late Neolithic/Chalcolithic basalt axe factory in the Manasseh Hills in Israel and suggest it had a primary role in the region for the production of these functional and symbolic tools. The form of discarded roughouts and flakes is used to deduce the principal eventual product and its sequence of manufacture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 7 publications
(5 reference statements)
0
25
0
Order By: Relevance
“…Previous geochemical-mineralogical studies of basalt artefacts in the southern Levant concentrated mainly on the determination of the provenance of the artefacts, but these studies always had rather limited results due to the fact that basaltic rock extraction sites had not been identified (apart from the Late Neolithic-Early Chalcolithic extraction site at Giv'at Kipod, see Rosenberg et al 2008;Gluhak & Rosenberg 2013;Rosenberg & Gluhak 2016;Shimelmitz & Rosenberg 2016) and that geochemical data from geological samples for comparison were, if available at all, only superficially included (e.g., Amiran & Porat 1984;Philip & Williams-Thorpe 1993;2000;2001;Rowan 1998;Rutter 2003;Rutter et al 2003;Watts et al 2004;Rutter & Philip 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous geochemical-mineralogical studies of basalt artefacts in the southern Levant concentrated mainly on the determination of the provenance of the artefacts, but these studies always had rather limited results due to the fact that basaltic rock extraction sites had not been identified (apart from the Late Neolithic-Early Chalcolithic extraction site at Giv'at Kipod, see Rosenberg et al 2008;Gluhak & Rosenberg 2013;Rosenberg & Gluhak 2016;Shimelmitz & Rosenberg 2016) and that geochemical data from geological samples for comparison were, if available at all, only superficially included (e.g., Amiran & Porat 1984;Philip & Williams-Thorpe 1993;2000;2001;Rowan 1998;Rutter 2003;Rutter et al 2003;Watts et al 2004;Rutter & Philip 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As no waste from basalt tool production was found, it is likely that all or at least a large part of the production sequence of these tools was conducted at quarry and production sites, and possibly transported as finished items to Ashqelon Barnea (e.g. Abadi-Reiss and Rosen 2008;Rosen 2002;Rosen and Schneider 2001;Rosenberg et al 2008;see Schneider 1993;1994 for discussions and additional data concerning quarry and production sites). Nonetheless, the possibility of nearly finished items reaching the site for their final finishing stage and later distribution to other sites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a variety of raw materials to manufacture a specific tool type characterized the production of bifacial tools in the southern Levant. Although primarily made of flint (e.g., Barkai 2005), some were produced on basaltic rocks, limestone, and other more 'exotic' raw materials (e.g., Garfinkel & Dag 2006;Rosenberg et al 2008;Rosenberg & Gopher 2010;Gluhak & Rosenberg 2013;Rosenberg and Gluhak 2015;Vardi 2015).…”
Section: Raw Materials and Bifacial Tools In The Southern Levantmentioning
confidence: 99%
“…20 km east of the Mediterranean Sea shoreline (Figure 1). The site has been explored since 2005 and both surveys and excavations revealed that it was a major extraction site for the production of bifacial tools (Shimelmitz et al 2005;Rosenberg et al 2008). The hill is one of several isolated igneous rock hills found along the southwestern margins of the Jezreel Valley.…”
Section: Giv'at Kipodmentioning
confidence: 99%
See 1 more Smart Citation